2016
DOI: 10.1080/13543776.2017.1276565
|View full text |Cite
|
Sign up to set email alerts
|

Selective histone deacetylase small molecule inhibitors: recent progress and perspectives

Abstract: Since the first pan-HDAC inhibitor SAHA was approved by U.S. FDA 10 years ago, HDACs including SIRT1-7 have received significant attention due to the fact that aberrant histone deacetylase activtiy has been implicated in a variety of human diseases, such as cancers, virus infection, and neurodegenerative diseases. During the past years, a considerable achievement of development of isoform- or class-selective HDAC inhibitors has been made, yielding many drug candidates for further clinical studies, which repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…HDAC1 has been served as a target for cancer therapy, and some small molecule HDAC inhibitors have been used in clinical treatment of patients with several types of cancer, such as T-cell lymphoma and multiple myeloma. [ 27 ] Consistent with this, the present analysis revealed the important clinical value of HDAC1 expression in lung cancer. In conclusion, HDAC1 expression might be a good biomarker for the diagnosis and prognosis of patients with lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…HDAC1 has been served as a target for cancer therapy, and some small molecule HDAC inhibitors have been used in clinical treatment of patients with several types of cancer, such as T-cell lymphoma and multiple myeloma. [ 27 ] Consistent with this, the present analysis revealed the important clinical value of HDAC1 expression in lung cancer. In conclusion, HDAC1 expression might be a good biomarker for the diagnosis and prognosis of patients with lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous clinical trials have been performed to identify clinical activity of HDAC inhibitors in patients with solid tumors. Although HDAC inhibitors have shown success in preventing graft versus host disease (GVHD) [ 61 ] and treating patients with T-cell lymphoma [ 62 ] and multiple myeloma [ 63 , 64 ]; to date, no study has shown significant benefit in patients with solid tumors [ 65 , 66 ]. We sought to explore the potential for HDAC inhibition to reverse chemoresistance based on promising results seen in animal models of leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The best studied epigenetic histone mark is acetylation; the addition and removal of acetyl groups occurs via the action of histone acetyltransferases and histone deacetylases. This is of particular clinical relevance, as histone deacetylases are the target of a number of drugs, mostly used as cancer therapy [66]. There are 18 human histone deacetylases (HDACs), falling into four broad classes, and several studies have examined the impacts of HDAC inhibitors on bone formation and maturation.…”
Section: Epigenetics In Bone Remodelingmentioning
confidence: 99%